2015
DOI: 10.1002/dev.21328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal factors and temperament on infant cortisol regulation in low‐income Mexican American families

Abstract: Prenatal psychosocial exposures can significantly affect infant health and development. Infants with higher temperamental negativity are theorized to be more susceptible to environmental exposures. We evaluated the interaction of prenatal maternal exposures and infant temperamental negativity to predict infant cortisol response to mildly challenging mother-infant interaction tasks. Participants included 322 Mexican American mother-infant dyads (mother age 18–42; 82% Spanish-speaking; modal family income $10,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…We treated postpartum depressive (PPD) symptoms at 6 weeks as a potential confound because prior research supports the association of PPD with maternal stress, social support, and cortisol. 17,19,3335 Therefore, we adjusted for six week depressive symptoms in the prediction of maternal cortisol at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…We treated postpartum depressive (PPD) symptoms at 6 weeks as a potential confound because prior research supports the association of PPD with maternal stress, social support, and cortisol. 17,19,3335 Therefore, we adjusted for six week depressive symptoms in the prediction of maternal cortisol at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal. Studies (n = 2) conducted in the prenatal period found a significant relationship between prenatal depressive symptoms and infant self-regulation [56,57]. In Fuller et al's study, higher prenatal maternal depressive symptoms on a continuum (Patient Health Questionnaire-9, score range 5-27) positively moderated the relationship between neighborhood stress and infant self-regulatory difficulties (IBQ-R).…”
Section: Socioemotional Outcomesmentioning
confidence: 96%
“…through dysfunctional cortisol responses: heightened cortisol output for 12-week old infants with high temperamental negativity but blunted cortisol for infants with low negativity [57]. Both studies co-varied for postpartum depressive symptoms, suggesting that dysfunctional self-regulatory processes were associated with the prenatal rather than postnatal psychosocial environment.…”
Section: Plos Onementioning
confidence: 96%
“…Indeed, findings from animal studies have indicated that pre- and postnatal stress may exert opposing influences on offspring epigenetic changes, suggesting that postnatal stress may reprogram changes that emerge initially as a result of exposure to prenatal stress (Bale, 2015). Nonetheless, evidence for high rates of stability between prenatal and postnatal stress, associations between early infant negativity and decreased maternal postnatal well-being and subsequent parenting quality underscore that the influence of prenatal stress on infant development may be enduring beyond the transmission of its effects on earlier to later negativity (Luecken et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For example, although aspects of Mexican American culture may protect against the adverse influence of prenatal stress on infant birth outcomes (Luecken et al, 2013; Ruiz, Hamann, Mehl, & O’Connor, 2016), prenatal stress exposure has nonetheless been found to compromise infants’ stress reactivity and regulation and the subsequent caregiving environment (Luecken, MacKinnon, Jewell, Crnic, & Gonzales, 2015). Likewise, although some scholars have found evidence suggestive that Mexican American children’s social skills may rival those of their socioeconomically advantaged, White counterparts (Guerrero et al, 2013), others have found that impoverished Latino children may nonetheless be equally susceptible to the influence of poverty on heightened rates of behavioral symptoms (e.g., Holtz, Fox, & Meurer, 2015).…”
Section: Socioemotional Developmental Processes In Disadvantaged Popumentioning
confidence: 99%